(untitled) (Eurasian Journal of Philology Science and Education, 2022)
An article about the study of vocabulary of Turkish origin, consumed by local American Indians. In this regard, this article explored the life, lifestyle, customs and traditions of the American Indians. The article explores the history, the development path of Indian tribes and the impact of this development on the lexical level, the similarities of the vocabulary of Turkish and Indian languages. The study of these facts arouses particular interest in studying the cause and conditions that give rise to their occurrence. In this sense, undoubtedly, the study of existing similarities and parallelism between the lexical systems of the Turkish and Indian languages is of great importance. Genetically, Indians are also closely related to the non-Turkic population of the Siberian-Altai Territory, for example, the Ket peoples, who belonged to the Yenisei language family. In Kets woman’s the percentage of haplotypes Q (95%) is as high as that of Indians. Nevertheless, most of the ancient peoples of the Yenisei were mixed with Siberian-Altaic Turks and took part in the ethnogenesis of the Yakuts, Tivas, Khakas, and Altai peoples. From the Yenisei languages to the present day only the language of the Kets has been preserved and in this language speaks from 10 to 15 people.